O direito constitucional à educação da pessoa com deficiência: construção de rampas digitais - Urnikes, Isabella Costa (2023)
This dissertation aims to present technology as an apparatus for the educational inclusion of the person with disability, starting from the presentation of the configuration of accessibility in the Brazilian constitutional legal system and the need for its observance in the technological-digital environment, as a way to make the constitutional right to education of the person with disability effective. Doctrinal and legislative studies involving the fundamental guarantees will be investigated, in addition to the Brazilian Federal Constitution of 1988, also covering infraconstitutional laws, administrative rules and international treaties. In view of this, the purpose of the proposed work is to point out the need to consider the right to accessibility in the digital environment as a measure to ensure the effectiveness of the equality principle, bringing to discussion studies on legal guarantees and pointing out the distinction between promoting and facilitating access and permanence in school for people with disabilities. As for the methodology used, this is qualitative research, whose data provides details and depth of knowledge for a better understanding of the implications presented. The focus of the dissertation is on the subjective character of the object, on the study of its particularities and on individual experiences. The discussion process is dialectic, for a certain reality is analyzed, confronting thesis and antithesis, seeking synthesis, aiming to contribute to the improvement of the process in the area of the rights of people with disabilities. Finally, the study relies on the bibliographic technique, applied both by means of direct and indirect analysis of the works of doctrinaire, of research to the works of national and international researchers dedicated to the theme